Simulation Models For Three-Phase Grid Connected PV Inverters Enabling Current Limitation Under Unbalanced Faults - Lam, L. H.; Phuc, T. D. H.; Hieu, N. H. (Engineering, Technology & Applied Science Research, 2020)
Normally unbalanced grid voltage dips may lead to unbalanced non-sinusoidal current injections, DC-link voltage oscillations, and active and/or reactive power oscillations with twice the grid fundamental frequency in three-phase grid-connected Photovoltaic (PV) systems. Double grid frequency oscillations at the DC-link of the conventional two-stage PV inverters can further deteriorate the DC-link capacitor, which is one of the most important limiting components in the system. Proper control of these converters may efficiently address this problem. In such solutions, Current Reference Calculation (CRC) is one of the most important issues that should be coped with the reliable operation of grid-connected converters under unbalanced grid faults. Therefore, this paper proposes and simulates CRC methods and presents the results in order to improve the quality of the grid-connected PV system under unbalanced grid voltage fault.